A Qualidade De Vida Nos Portadores De Diabetes Mellitus Do Tipo 2. - Mansur, Angelita Da Silva (2024)
Diabetes mellitus is characterized as a public health problem due to the increasing of its incidence and prevalence. As it is a progressive disease, those affected tend to deteriorate their health over time, leading to the development of complications caused by poor glycemic control. This study aimed to assess the health-related quality of life, overall and considering its physical and mental components, and the possible associations with sociodemographic and clinical information of type 2 diabetes mellitus patients from a University Hospital in a southeastern capital of Brazil. This is an observational, cross-sectional analytical study. Data were collected from 300 patients through interviews that gathered sociodemographic and clinical information. The SF36 questionnaire was used to assess health-related quality of life, which is a generic instrument composed of 11 questions and 36 items, divided into eight domains. Analyses were performed using the T-test and multivariate logistic regression models, considering a confidence level of 95%. The scores obtained for the SF-36 domains showed that patients had a high score for quality of life associated with Social Aspects and a lower score for the Physical Functioning domain, indicating that patients' physical limitations negatively impact their quality of life. In the analysis of the relationship between the variables and SF-36 domains, for most of the variables, the difference between the means of the categories was statistically significant for the domains of Functional Capacity and Pain. Logistic regression results indicated that age, education level, and physical activity were variables that influenced the likelihood of obtaining better physical and mental quality of life. Additionally, in relation to physical quality of life, marital status was statistically significant. Identifying factors associated with the quality of life of patients with diabetes mellitus contributes to understanding the implications of the disease and may help bridge the gap between diagnosis and treatment adherence.